INFLUENCE OF FERTILIZERS ON YIELD AND QUALITY INDICATORS OF GRAIN WINTER WHEAT - Кудрявицька, Аліна; Карабач, Катерина (SWorldJournal, 2023)
On black carbonate soil it is set researches, that the protracted application of mineral fertilizers is on a background the afteraction of organic, the Миронівська furious provides the increase of harvest of grain of the districted sort of furious wheat o